Early Catholicism and the organisational structure of the United Methodist Church in Zimbabwe - Mashero, Edward; van Eck, Ernest (Theologia Viatorum (Sorenga), 2021)
The organisational structure of the United Methodist church shares many features with the early catholic institutions. Increased institutionalisation, that is, authority connected with office, is the clearest sign of Early Catholicism. By the late first century, the titles of bishop (ἐπίσκοπος), elder (πρεσ[Beta]ύτερος) and deacon (διάκονος) denoted specific leadership and service functions in the church. This study stresses the ethical qualifications and diaconal duties of these office bearers, applying it to the duties and responsibilities of United Methodist pastors, district superintendents, bishops and laity. It is argued that candidates for ordination should be aware of their calling to the divine ministry and their calling should be authenticated and recognised without a test of authenticity by the Church. In the Early Catholicism period, qualified leadership was established to preserve faith and combat false teaching. This must also be the case in the United Methodist Church.